EFFECTIVENESS OF DISPOSABLE MEDICAL DEVICE PROCUREMENT IN INCREASING THE ACCELERATION OF THE USE OF DOMESTIC PRODUCTS IN RSUD BALI MANDARA - Kristanti, I Gusti Ayu Made Iin; Senastri, Dr. Ni Made Jaya; Arjaya, Dr. I Made (jfpublisher, 2024)
During the early days of the Covid-19 pandemic, there were a number of medical device vacancies that impacted health services. This situation urged the government to fulfill the need for domestic medical devices. This is what underlies the establishment of Presidential Instruction No. 2/2022 concerning Acceleration of Increased Use of Domestic Products. The purpose of this research is to analyze the regulation of the procurement of disposable medical devices in order to increase the acceleration of the use of domestic products and analyze the factors that influence the emergence of obstacles in the implementation of Presidential Instruction No. 2/2022 at RSUD Bali Mandara (Bali Mandara Regional General Hospital). This research applies empirical legal research methods, using statutory, conceptual, and sociological approaches. The implementation of the regulation to purchase domestically produced disposable medical devices at RSUD Bali Mandara is conducted by adhering to Presidential Instruction No. 2/2022, with the aim of increasing the use of domestically produced disposable medical devices in the hospital environment. However, during its implementation at RSUD Bali Mandara, there were several obstacles related to the purchase of domestically produced disposable medical devices. These obstacles include limited stock, users concerns regarding quality, and price differences that make domestic products more expensive compared to the imported products.